How Professionals Adapt to Artificial Intelligence: The Role of Intertwined Boundary Work - Faulconbridge, James; Sarwar, Atif; Spring, Martin (Journal of Management Studies, 2025)
AbstractThe rise of artificial intelligence (AI) has generated extensive debates about the future of work in the professions. However, few studies take account of the potential for AI's disruptive effects to trigger robust defence by professionals of their interests and resources. By examining the adoption of AI in accounting and law professional service firms (PSFs), we show how professionals respond through intertwined boundary work, this being the process by which professionals respond to disruptions and protect interests and resources by engaging in multiple interdependent modes of boundary work. We also examine the way professionals collaborate with other groups as part of intertwined boundary work, and the implications for some key features of PSF organization. Our study reveals that the responses of professionals to AI are leading to new types of professional work and services. This means that rather than spelling the ‘end of the professions’, AI is leading to reconfigured forms of professional activity, jurisdiction, and PSFs.